Some Economical and Informational Aspects of the e-Business - Zenon Biniek (Contemporary Economics)
In the article, it has undertaken the task of describing the most important economic and information processing aspects of the e-business. It has shown contemplation for the topic of effects, which can occur in case with current initiating electronic nets of distribution and related with this, net business (Webeconomics). Besides it has included the set of postulates, which, information system technology must be implement, to equal e-business challenges. It has shown group of features of rich internet application.